System Trust Researching the Architecture of Trust in Systems - Sumpf, Patrick; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
Frequently enabled by digitalization, great transformations are taking place in socio-technical systems such as energy, telecommunications, and mobility. These transformations indicate widespread shifts in societal infrastructure systems, rearranging relations between governments, industries, NGOs, and consumers. In this context, the question of trust in systems - as introduced by sociologists Luhmann, Coleman and Giddens - acquires new urgency, as yet uncommented upon in trust research, or socio-technical systems debates. Focusing on the energy sector, Patrick Sumpf analyzes the meanings of system and trust to develop a framework for both theoretical and empirical research, which is synthesized into an "Architecture of Trust" in systems. Contents The Dualism of System Trust Intersections in Trust Research Open and Closed Systems System Identity Toward an 'Architecture of Trust' Case Study: Trust in the Energy System Target Groups Researchers and students in sociology, communications, psychology, management, trust research, and energy research Consultants in energy policy and management The Author Patrick Sumpf holds a Dr. phil. in media and communication studies from Mannheim University, Germany. He is a research associate and project lead at the Institute for Technology Assessment and Systems Analysis (ITAS), Karlsruhe Institute of Technology (KIT).
The Dualism of System Trust -- Intersections in Trust Research -- Open and Closed Systems -- System Identity -- Toward an 'Architecture of Trust' -- Case Study: Trust in the Energy System.
Keywords: Sociology; Sociology -- Methodology; Science -- Social aspects; Sociological Theory; Sociological Methods; Science and Technology Studies